2009
DOI: 10.1126/science.1169754
|View full text |Cite
|
Sign up to set email alerts
|

A Global View of the Lithosphere-Asthenosphere Boundary

Abstract: The lithosphere-asthenosphere boundary divides the rigid lid from the weaker mantle and is fundamental in plate tectonics. However, its depth and defining mechanism are not well known. We analyzed 15 years of global seismic data using P-to-S (Ps) converted phases and imaged an interface that correlates with tectonic environment, varying from 95 +/- 4 kilometers beneath Precambrian shields and platforms to 81 +/- 2 kilometers beneath tectonically altered regions and 70 +/- 4 kilometers at oceanic island station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
298
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(324 citation statements)
references
References 29 publications
25
298
1
Order By: Relevance
“…Observations of the LAB in P receiver functions are not unusual. Such observations have also been obtained worldwide by Rychert and Shearer (2009). S receiver functions are very useful for the verification of LAB observations, because of the absence of multiples (see e.g.…”
Section: Validation Assessment Of the Moho Lab 410 Km And 660 Km DImentioning
confidence: 99%
“…Observations of the LAB in P receiver functions are not unusual. Such observations have also been obtained worldwide by Rychert and Shearer (2009). S receiver functions are very useful for the verification of LAB observations, because of the absence of multiples (see e.g.…”
Section: Validation Assessment Of the Moho Lab 410 Km And 660 Km DImentioning
confidence: 99%
“…On the other hand the values provided by Dundar et al (2011) using S-wave receiver functions and by a recent Rayleigh wave tomography ) are similar to ours. Rychert & Shearer (2009) have compiled a global map of the LAB depth from P receiver function observations. They found LAB depths of 80-95 km under active tectonic areas.…”
Section: A Shallow Lithosphere-asthenosphere Boundary (Lab)mentioning
confidence: 99%
“…Recent studies have suggested a thickness of 200-250 km by incorporating the effects of anisotropy on seismic velocities 61 . However, at shallower depths (100-140 km) beneath these cratons, strong conversions from compressional-to-shear wave (P-S) and shear-to-compressional wave (S-P) have been found [62][63][64] . This led some researchers to believe that the thickness of the cratonic lithosphere might be less than expected 62 , which contradicts tomographic and other geophysical and geochemical observations.…”
Section: Stability Of Cratonsmentioning
confidence: 99%
“…However, at shallower depths (100-140 km) beneath these cratons, strong conversions from compressional-to-shear wave (P-S) and shear-to-compressional wave (S-P) have been found [62][63][64] . This led some researchers to believe that the thickness of the cratonic lithosphere might be less than expected 62 , which contradicts tomographic and other geophysical and geochemical observations. Therefore, such conversions have been recently attributed to the presence of an intracontinental discontinuous zone of either partial melt or dehydrated material, or both, around depths of 100 km (ref.…”
Section: Stability Of Cratonsmentioning
confidence: 99%